Cost-Effectiveness Analysis of Diagnosis of Duchenne/Becker Muscular Dystrophy in Colombia (2018)
Objectives: To determine the cost-effectiveness ratio of different courses of action for the diagnosis of Duchenne or Becker muscular dystrophy in Colombia. Methods: The cost-effectiveness analysis was performed from the Colombian health system perspective. Decision trees were constructed, and different courses of action were compared considering the following tests: immunohistochemistry (IHC), Western blot (WB), multiplex polymerase chain reaction, multiplex ligation-dependent probe amplification (MLPA), and the complete sequencing of the dystrophin gene. The time horizon matched the duration of sample extraction and analysis. Transition probabilities were obtained from a systematic review. Costs were constructed with a type-case methodology using the consensus of experts and the valuation of resources from consulting laboratories and the 2001 Social Security Institute cost manual. Deterministic sensitivity and scenario analyses were performed with one or more unavailable alternatives. Costs were converted from Colombian pesos to US dollars using the 2014 exchange rate. Results: In the base case, WB was the dominant strategy, with a cost of US $419.07 and a sensitivity of 100%. This approach remains the dominant strategy down to a 98.2% sensitivity and while costs do not exceed US $837.38. If WB was not available, IHC had the best cost-effectiveness ratio, followed by MLPA and sequencing. Conclusions: WB is a cost-effective alternative for the diagnosis of patients suspected of having Duchenne or Becker muscular dystrophy in the Colombian health system. The IHC test is rated as the second-best detection method. If these tests are not available, MLPA followed by sequencing would be the most cost-effective alternative. © 2018